Trade liberalization, factor market flexibility, and growth : the case of Morocco and Tunisia - Dennis, Allen Curtis (Policy research working paper, 2006)
"In recent years there has been an increasing recognition of the importance of complementary policies in enhancing the benefits of a more open trade regime. This study focuses on the importance of factor market flexibility to trade reforms. Using the Global Trade Analysis Project (GTAP) model and database, the results show that the welfare impact of trade reform is contingent on the flexibility of factor markets, with higher welfare gains occurring where factor markets are more flexible, and vice-versa. Defining two extreme factor market scenarios over Morocco and Tunisia, the author finds that the welfare gains of trade reforms under conditions of flexible factor markets can be as much as six times the gains compared with a rigid factor market scenario. This is so because whereas trade reforms may improve the incentive structure for resource reallocation, the extent to which resources move from less efficient to more efficient sectors of an economy is dependent on the degree of flexibility of factor markets. "--World Bank web site